An Exploratory Study of Transgender Inmate Populations in Latin America. (3rd July 2020) - Johnson, Richard Greggory; McCandless, Sean; Renderos, Hugo
Abstract : Transgender persons disproportionately face inequities, especially in prisons. Despite these inequities, the academic literature on this topic is limited. Even more limited is the literature on transgender issues in Latin America. This exploratory study addresses these issues. First, it examines literature on transgender prisoners, emphasizing how they, already victimized by society at large, are revictimized in prisons. Second, it investigates the experiences of transgender prisoners in Latin America, specifically El Salvador and Nicaragua. These countries serve as potent test cases to examine how societal, legal, and systemic prejudices intersect to revictimize a vulnerable population. Third, this article analyzes interviews with five formerly imprisoned transgender women in these countries. The women detail reasons for their imprisonment and experiences therein. Fourth, policy recommendations are offered.